FOXO3 gene polymorphisms influence the risk of acute lymphoblastic leukemia in Chinese children. Issue 2 (6th November 2019) - Yang, Xu; Wu, Xuedong; Fang, Na; Liu, Xiaoping; Liu, Xiaodan; Yang, Lihua; Huang, Ke; Luo, Ailing; Cai, Mansi; Wu, Fan; Jiang, Hua; Xu, Ling
Abstract: Acute lymphoblastic leukemia (ALL) is the most frequently diagnosed cancer in children and single‐nucleotide polymorphisms (SNPs) in certain genes influence risk of ALL. Although FOXO3 had been demonstrated to be involved leukemia, the role of FOXO3 polymorphisms was still not clear. In the present study, we explored the association of FOXO3 SNPs with ALL risk in Chinese children. We genotyped four polymorphisms (rs17069665 A>G, rs4945816 T>C, rs4946936 C>T, and rs9400241 A>C) of FOXO3 in 425 ALL cases and 1339 health controls. The associations were estimated by odds ratios (ORs) with their 95% confidence intervals (CIs). Further analyses were performed to explore associations of rs17069665 and rs9400241 with ALL susceptibility in terms of age, gender, immunophenotype, minimal residual disease (MRD), and other clinical characteristics. We found rs17069665 related to the increased ALL risk (OR = 1.76; 95% CI = 1.02‐3.04), rs9400241 related to decreased ALL risk (OR = 0.80; 95% CI = 0.64‐0.99). The effects of rs17069665 on ALL risk were more predominant in males and children < 10 years, and patients with lower rates of platelet or neutrophil. As for rs9400241, the effects were more predominant in children < 10 years, and in patients with pre B ALL, positive MRD, anemia, or hepatomegaly. In conclusion, FOXO3 gene polymorphisms influence the risk of ALL in children and might be a potential biomarker for ALL susceptibility. Abstract : FOXO3 gene polymorphisms influence the risk of acute lymphoblastic leukemia in Chinese children.The rs17069665 G allele was related to an increased acute lymphoblastic leukemia (ALL) risk, while rs9400241 C allele related to a decreased ALL risk.